2010
DOI: 10.1073/pnas.1001069107
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the protectors path from the germ line to the genome

Abstract: One of the basic principles that nature uses in evolution is to recycle successful concepts and create new functions by modifying existing units. This conservatism in evolution has resulted in an astonishingly high sequence identity of genes, even between evolutionarily distant species such as the nematode Caenorhabditis elegans and Homo sapiens. The recycling of successful concepts in conjunction with gene duplication events has also led to the existence of highly homologous proteins within the genome of many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 134 publications
0
15
0
Order By: Relevance
“…16 Drosophila p53 is more similar to human p53 in that it lacks the SAM protein-interaction domain found in the C-terminus of p63 and p73. 7,[34][35][36][37] Orthologs in many invertebrates, including ciliates, contain a SAM domain, suggesting that the p63 paralogs represent an ancestral form. 7,36,37 Each of the orthologs in Molluscs and some Arachnids also encode multiple protein isoforms, suggesting that this property is an ancient attribute of the p53 gene family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Drosophila p53 is more similar to human p53 in that it lacks the SAM protein-interaction domain found in the C-terminus of p63 and p73. 7,[34][35][36][37] Orthologs in many invertebrates, including ciliates, contain a SAM domain, suggesting that the p63 paralogs represent an ancestral form. 7,36,37 Each of the orthologs in Molluscs and some Arachnids also encode multiple protein isoforms, suggesting that this property is an ancient attribute of the p53 gene family.…”
Section: Discussionmentioning
confidence: 99%
“…7,[34][35][36][37] Since the initial description of Drosophila p53, most investigations into its function have focused on a single 44 kD protein isoform, but expression of a 56 kD isoform has also been described. 15,34,35,38 The current genome annotation based on deep RNA sequencing predicts four mRNA isoforms (A, B, C, and E) and three proteins, with transcript A and C encoding the same well-characterized 44 kD protein 39,40 ( Figure 1a).…”
mentioning
confidence: 99%
“…12,13 In the starlet sea anemone, UV-induced germ cell death requires the function of the p53 ortholog nvp63.…”
mentioning
confidence: 99%
“…Detailed functional and structural investigations of p63 and p73, two homologs of the tumor suppressor protein p53, have suggested that p63 is the most ancient member of this protein family, from which the other members have evolved. [1][2][3] This idea was particularly fueled by the discovery that invertebrates like Caenorhabditis elegans have p53-like proteins [4][5][6] that are more closely related to p63 than to p53. [7][8][9] In C. elegans the Cep-1 protein does not act as a tumor suppressor but is expressed in germ cells where it serves as a quality control factor.…”
mentioning
confidence: 99%